2014
DOI: 10.1111/ppa.12247
|View full text |Cite
|
Sign up to set email alerts
|

Latent entry and spread ofColletotrichum acutatum(species complex) in strawberry fields

Abstract: Anthracnose, caused by Colletotrichum acutatum (species complex), has become a troublesome problem in strawberry production worldwide. This paper reports (i) an optimized sampling method combined with a real‐time PCR technique to detect the latent presence of C. acutatum in cold‐stored strawberry plants used as planting material in several European countries, and (ii) a study of the spread of C. acutatum following a point inoculation under field conditions. Screening of different parts of planting material sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Strawberry (Fragaria × ananassa) is an important soft fruit crop that is popular all over the world. Gray mold is a serious disease in strawberry production and leads to important economic losses (Debode et al, 2015;Petrasch et al, 2019). B. cinerea can infect all plant parts of strawberry including leaves, fruits, flowers, petioles, and stems at every growth stage (Williamson et al, 2007;Petrasch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry (Fragaria × ananassa) is an important soft fruit crop that is popular all over the world. Gray mold is a serious disease in strawberry production and leads to important economic losses (Debode et al, 2015;Petrasch et al, 2019). B. cinerea can infect all plant parts of strawberry including leaves, fruits, flowers, petioles, and stems at every growth stage (Williamson et al, 2007;Petrasch et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The plausible explanation for differences in detection from different leaf stages receiving same initial inoculum in our study could be due to young stage leaf may not be providing enough nutrients for the growth and development of the fungus and old stage leaf may contain higher concentration of inhibitory metabolites that may interfere with PCR amplification. Debode et al [23] [38] reported a slower establishment of C. acutatum on younger leaves compared to older from the leaf inoculation experiment followed by monitoring through microscopic study and DNA extraction. Similar effects of leaf age on disease development were observed with C. gloeosporioides on leaves of Mulva pusilla [39].…”
Section: Discussionmentioning
confidence: 99%
“…The fungus is mainly dispersed by rain, and can enter the host via any plant tissue. Dispersal of conidia can reach as far as 1.75 m through splashing and the infection of one plant in the field by the pathogen proceeds to the whole cultivation [57]. Most frequently C. acutatum infects strawberries through the crown, as there is a humid microclimate [58].…”
Section: Fungal Pathogens—characteristics Occurrence Properties mentioning
confidence: 99%